Amyloid Beta (Aβ) Peptide and Factors that Play Important Roles in Alzheimer’s Disease - Jamasbi, Elaheh; D. Wade, John; Separovic, Frances; A. Hossain, Mohammed (Current Medicinal Chemistry, 2016)
Amyloid beta peptide (Aβ) is recognised as a main feature of Alzheimer’s disease (AD). Increasing evidence suggests that small soluble oligomers of Aβ are the toxic form of the peptide and may instigate AD. Different factors including some key residues within Aβ molecule, the cell membrane, prion protein and metals play important roles in developing AD. Significant progress has been made to understand these factors and elucidate the mechanism of cytotoxicity of Aβ. This review summarizes recent findings in the area of Aβ and AD research, and this current knowledge could enable medicinal chemists to design and develop therapeutics to treat AD.
Keywords: oligomers